Copper-Impregnated Magnetite as a Heterogeneous Catalyst for the Homocoupling of Terminal Alkynes - Pérez, Juana M.; Cano, Rafael; Yus, Miguel; Ramón, Diego J. (Synthesis, 2013)
Copper-impregnated magnetite is a versatile heterogeneous catalytic system for the synthesis of 1,3-diynes by the homocoupling of terminal alkynes. This catalyst does not require the use of pressurized oxygen as the oxidant and it does not need a solvent or harsh conditions to give the expected products. Moreover, the catalyst can be removed from the reaction medium simply by using a magnet. The reaction occurs at the lowest copper loading reported for any heterogeneous catalyst.
Keywords: alkynes; copper; heterogeneous catalysis; iron; supported catalysis; coupling; furans